2012
DOI: 10.1111/pan.12048
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Can't Intubate Can't Oxygenate’ scenario in Pediatric Anesthesia: a comparison of different devices for needle cricothyroidotomy

Abstract: Cannula tracheotomy in a model comparable to the infant airway is difficult and not without complication. Cannulae of 14- and 18-gauge appear to offer similar performance. Successful aspiration is the key predictor of appropriate cannula placement. The Quicktrach Child was not used successfully in this model. Further work is required to compare possible management strategies for the CICO scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 11 publications
0
35
1
2
Order By: Relevance
“…However, Stacey et al reported that cannula tracheostomy in a model comparable to an infant’s airway was still difficult and not performed without complication [5]. Because little evidence exists to guide the management of the “can’t intubate, can’t oxygenate” scenario in pediatric anesthesia [1], weight may not predict appropriate timing for general anesthesia in an infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Stacey et al reported that cannula tracheostomy in a model comparable to an infant’s airway was still difficult and not performed without complication [5]. Because little evidence exists to guide the management of the “can’t intubate, can’t oxygenate” scenario in pediatric anesthesia [1], weight may not predict appropriate timing for general anesthesia in an infant.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is little clinical or experimental evidence to guide the management of the “can’t intubate, can’t oxygenate” (CICO) scenario in pediatric anesthesia particularly regarding the infant or neonate [1]. We describe here an infant with facial vascular malformation.…”
Section: Introductionmentioning
confidence: 99%
“…have mentioned that cricothyroidotomy can be dangerous in children and a surgical tracheostomy is the method of choice. [222324] During tracheostomy, attempt should be made to maintain oxygenation by keeping the upper airway patent and continuously administering 100% oxygen.…”
Section: Emergency Surgical Airway Accessmentioning
confidence: 99%
“…Los estudios iniciales en modelos animales sugieren que la cricoidotomía quirúrgica puede ser superior a la técnica con aguja en pacientes preescolares 16,17 ; incluso en pacientes adultos, la cricoidotomía con aguja también ha mostrado poco éxito 18,19 , aunque sigue siendo una alternativa dentro del algoritmo de la vía aérea para proveer oxigenación por unos minutos. Estas técnicas son medidas desesperadas que no pueden hacernos olvidar que lo más importante siempre es mantener la ventilación y la oxigenación, antes que lograr la intubación de la tráquea.…”
Section: Obstrucción Funcional De La Vía Aéreaunclassified
“…La ventilación con máscara facial puede ser optimizada al utilizar dispositivos como las cánulas orofaríngea o nasofaríngea, la ventilación a 4 manos o el uso de un dispositivo supraglótico como la máscara laríngea 17 . Un cirujano debe estar presente en aquellos pacientes que cursan con gran edema de la vía aérea o que tienen antecedentes claros y conocidos de ventilación con máscara facial difícil y cuando la oxigenación se deteriora con rapidez.…”
Section: Vía Aérea Difícil Esperada O Anticipadaunclassified